Assessing economic impacts and returns to investment in Boro rice research and extension in Bangladesh - Islam, Mohammad Samiul; Kamarulzaman, Nitty Hirawaty; Shamsudin, Mad Nasir; Mohd Nawi, Nolila; Alam, Mohammad Jahangir; Bhandari, Humnath (Global Academic Excellence, 2024)
This study quantifies the impact and returns on investment from Boro rice breeding research and extension in Bangladesh from 1971 to 2022 using the economic surplus model and project evaluation techniques. The purpose of the study is to assess the economic impact and effectiveness of public investments in rice breeding research and extension, providing insights for future policy and funding decisions. The novelty of this study lies in its comprehensive evaluation over 51 years, applying both closed and open economy perspectives to capture a broader range of benefits and potential savings. Results indicate that rice breeding research generated social benefits of Taka 1236.74 billion in a closed economy and Taka 1199.55 billion in an open economy, saving US$ 40.22 billion in foreign exchange. The investment yielded an estimated net present value (NPV) of Taka 1133.75 billion, an internal rate of return (IRR) of 75%, and a benefit-cost ratio (BCR) of 15. These findings underscore the need for increased public support for agricultural research in Bangladesh. However, benefits primarily accrued to consumers, with producers facing losses due to assumptions of a small, open economy and lower demand elasticity compared to supply. The study recommends increased investment in public rice research institutes for R&D and extension programs to achieve food self-sufficiency.